Information Systems for Crisis Response and Management in Mediterranean Countries Third International Conference, ISCRAM-med 2016, Madrid, Spain, October 26-28, 2016, Proceedings - Díaz, Paloma; Bellamine Ben Saoud, Narjès; Dugdale, Julie; Hanachi, Chihab (Lecture Notes in Business Information Processing, 2016)
This book constitutes the refereed proceedings of the Third International Conference on Information Systems for Crisis Response and Management in Mediterranean Countries, ISCRAM-med 2016, held in Madrid, Spain, in October 2016. Information systems and technologies can play a key role in crisis management in order to support preparation, response, mitigation and recovery processes. Yet technology is not enough to guarantee a better management process, and therefore the conference does not only focus on engineering technologies, but also on their application and practical experiences. The 12 full and 8 short papers presented in this volume were carefully reviewed and selected from 36 submissions. They are organized in topical sections on mobile apps for citizens, modeling and simulation, development of information systems, information and knowledge management, collaboration and coordination, social computing, and issues in humanitarian crisis.